2010
DOI: 10.1136/ip.2010.027011
|View full text |Cite
|
Sign up to set email alerts
|

A controlled evaluation of the WHO Safe Communities model approach to injury prevention: increasing child restraint use in motor vehicles

Abstract: The Safe Communities approach was successful in promoting the use of child restraints in motor vehicles through a multifaceted intervention that included efforts in various community settings, instructional classes and child safety seat distribution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…Furthermore, in Dallas (Texas), an interventional study showed that there was a significant increase in seat belt use among drivers due to the implementation of the Safe Community intervention. The Dallas study found seat belt use by drivers increased by 16% in the area in which the Safe Community intervention had been conducted, but only a 5% increase was observed in the comparison area (Istre et al, 2011).…”
Section: Resultsmentioning
confidence: 98%
“…Furthermore, in Dallas (Texas), an interventional study showed that there was a significant increase in seat belt use among drivers due to the implementation of the Safe Community intervention. The Dallas study found seat belt use by drivers increased by 16% in the area in which the Safe Community intervention had been conducted, but only a 5% increase was observed in the comparison area (Istre et al, 2011).…”
Section: Resultsmentioning
confidence: 98%
“…There were relatively few studies identified with three studies related to Active Living Communities [40][41][42]; one each for Safe communities [43] and Smart growth [44] and two related to Age Friendly Cities [45,46]. While various study designs were employed, none were randomized controlled trials.…”
Section: Safe Routes To Schoolmentioning
confidence: 99%
“…The review identified only one study in Texas that examined the effect of a community based intervention on the use of child restraints in motorized transport [43]. The authors found that the intervention positively influenced safety behaviors such as the use of child restraints, drivers using seat belts and children riding in the back seat.…”
Section: Safe Communitiesmentioning
confidence: 99%
“…Multifaceted education-based programs (Ehiri et al 2006) including child safety seat classes for parents (Apsler et al 2003;Brixey et al 2009;Istre et al 2002;Istre et al 2011), hands-on demonstrations (Istre et al 2002;Istre et al 2011), child restraint fitting checks (Istre et al 2011), or free or subsidized restraints (Apsler et al 2003;Brixey et al 2009;Istre et al 2002Istre et al , 2011 have been shown to positively affect ageappropriate restraint use (Apsler et al 2003;Brixey et al 2009;Istre et al 2002), but none of these activities have been trialed in communities with a large proportion of Aboriginal families. Furthermore, one study trialed a multifaceted approach yet did not find a positive outcome.…”
Section: Introductionmentioning
confidence: 98%